2010
DOI: 10.1055/s-0030-1255868
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for advanced lesions undetected at prior colonoscopy: not always poor preparation

Abstract: Failure to detect advanced neoplasia is common in a community-based endoscopy facility. Previously undetected advanced lesions are more frequently found in the left colon and rectum. Risk factors for non-detection of advanced adenoma are similar to those for advanced neoplasia recurrence. Lowering non-detection rates is crucial for correct follow-up recommendations. Patients should be aware of rates of detection of advanced neoplasia after previous normal colonoscopic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
10
1
1
Order By: Relevance
“…Although colonoscopy is the gold standard for colonic examinations, studies have shown that even advanced lesions may remain undetected 24. However, even if some of the lesions were missed lesions, the risk of developing CRC is still considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Although colonoscopy is the gold standard for colonic examinations, studies have shown that even advanced lesions may remain undetected 24. However, even if some of the lesions were missed lesions, the risk of developing CRC is still considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Cecal intubation, adequate bowel preparation, and a colonoscopic withdrawal time of 6 minutes or more are suggested to ensure complete removal of polyps and improvement of polyp detection based on previous studies 78. Despite these efforts, it has been reported that a significant number of polyps are missed during surveillance colonoscopy,91011121314151617 thereby leading to the development of interval cancers from the missed neoplastic polyps 18. Based on several tandem or consecutive colonoscopy studies,912131415 the miss rate of polyps is reported to be 16.8% to 28%.…”
Section: Introductionmentioning
confidence: 99%
“…La tasa de detección depende de factores como el test utilizado, la preparación efectuada para la limpieza intestinal y a la experiencia de los profesionales en la realización de colonoscopias 26 , por lo que es necesario auditar todos estos criterios y garantizar que el programa cumpla con los estándares de calidad. En nuestro caso, el mismo equipo de gastroenterólogos realizó las colonoscopias, independientemente del tipo de TSOH, por lo que el aumento observado en la tasa de detección es atribuible básicamen-te al tipo de test.…”
Section: Discussionunclassified